1993
DOI: 10.2527/1993.711199x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezing semen and dosage of sperm on number of accessory sperm, fertility, and embryo quality in artificially inseminated cattle1

Abstract: This experiment was conducted to determine whether use of fresh or frozen semen at either 20 x 10(6) (low) or 100 x 10(6) (high) sperm per dose affects the number of accessory sperm and fertilization status/embryo quality as determined from ova/embryos recovered nonsurgically 6 d after insemination. Ejaculates of four bulls were split and prepared for use as fresh or frozen semen at either the high or low dose. From 129 inseminations to normally cycling cows, 98 ova/embryos were recovered. To reduce male effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 13 publications
4
32
0
2
Order By: Relevance
“…In cattle, approximately 5000 unsorted sperm [23] and as few as 600 [24] or 1500 to 2250 sexed sperm [4] are sufficient to fertilize a bovine oocyte in vitro, whereas 20 million unsorted sperm [25] and 1 to 4 million of sorted and frozen sperm [13,26] are normally used per AI. In vitro production (IVP) of embryos with sex-sorted sperm could justify the use of this sperm despite its higher price.…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, approximately 5000 unsorted sperm [23] and as few as 600 [24] or 1500 to 2250 sexed sperm [4] are sufficient to fertilize a bovine oocyte in vitro, whereas 20 million unsorted sperm [25] and 1 to 4 million of sorted and frozen sperm [13,26] are normally used per AI. In vitro production (IVP) of embryos with sex-sorted sperm could justify the use of this sperm despite its higher price.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the hypothesis that the AR sperm found up to 5 h of incubation represent sperm killed by freezing, and supports the commercial practice of using more total frozen-thawed sperm than fresh sperm for insemination. However, with 10 x 10 6 or 100 x 10 6 sperm inseminated Nadir et al [30] found no difference between fresh and frozen semen in accessory sperm attached per egg.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy in estimating sperm number is important in ART (Evenson et al 1993, Hansen et al 2002, in the standardization of cryopreservation methods , for studies of environmental chemical impacts to reproductive health (Haubruge et al 2000, Eustache et al 2001, as well as in predicting fertility (Nadir et al 1993) and post-thaw survival (Centola et al 1992). No single counting method is uniformly preferred in andrology or research laboratories.…”
Section: Discussionmentioning
confidence: 99%